SHOPPING ORIENTATION AND SALES PROMOTION ON SALES PURCHASE INTENTION AT BLACKBERRY MESSENGER GROUP CLOTHING SALES IN MANADO - Suratman, Richo Eko (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Online shopping becomes a new phenomenon in the society due to the various benefits offered. Blackberry Messenger (BBM) as a chatting application began to be used by marketer to promote their products and to attract customers through the BBM group of online shop. People in Manado tend to fashionable, stylish, up to date about the trend, and consumptive, and therefore affect the consumer purchase intention. There are some factors which affect sales purchase intention some of them are shopping orientation and sales promotion. The main objective of this research is to know the effect of shopping orientation and sales promotion on sales purchase intention, in the case study at BBM group clothing sales in Manado partially and simultaneously. The population in this research is the people in Manado who had made online purchasing of clothing via BBM at least once. The samples of respondents are 100 respondents. This research used quantitative method with technique analysis is multiple regression analysis. The conclusion is shopping orientation and sales promotion effect the sales purchase intention both simultaneously and partially. This study suggest to the seller to pay attention to shopping orientation and sales promotion to increasing the sales. Keywords: shopping orientation, sales promotion, purchase intention